Pitch Angle Control for Variable Speed Wind Turbines - Mouna Ben Smida; Anis Sakly (Renewable Energy and Sustainable Development, 2015)
Abstract.Pitch control is a practical technique for power regulation above the rated wind speed it is considered as the most efficient and popular power control method. As conventional pitch control usually use PI controller, the mathematical model of the system should be known well. This paper deals with the operation and the control of the direct driven permanent magnet synchronous generator (PMSG). Different conventional strategies of pitch angle control are described and validated through simulation results under Matlab\Simulink.